Comparison of the distraction index and Norberg angle with radiographic grading of canine hip dysplasia - Carneiro, Rafael K. [UNESP]; da Cruz, Igor C.; Lima, Bruna [UNESP]; Aires, Luiz P. N. [UNESP]; Pompeu, Brenda [UNESP]; Ferreira, Márcio P.; Giglio, Robson F.; Uscategui, Ricardo A.; Minto, Bruno W. [UNESP]; Gasser, Beatriz; Feliciano, Marcus R. (Wiley, 2024)
The Orthopedic Foundation for Animals (OFA) radiographic grading system stands as a well-established benchmark for categorizing hip dysplasia in canines. Although more objective techniques to quantify early hip laxity in young dogs, such as the Norberg angle (NA) and distraction index (DI), have been documented, there is a scarcity of published studies that directly compare these radiographic measures. The primary objectives of this prospective, analytical study were to assess and compare the NA and DI measures with OFA grades within a cohort of dogs. Thirty dogs (57 hip joints) were evaluated, with a mean age of 5.4 ± 2.9 years and a mean body weight of 34.3 ± 7.1 kg. The discriminative power of hip dysplasia for DI and NA used OFA as a reference were compared by multivariate discriminant analysis test. Using the DI (≤0.3) 12 joints were classified as normal, using NA (≥105°) 24 joints and using OFA (≤3) 29. When comparing the discriminant power of NA with OFA resulting similar (P =.8324) with correct classifications of 81% using cross validation, however, the discriminant power of dysplasia of the DI resulted significantly greater (P =.0034) than OFA with correct classifications of only 59% using cross-validation, consequently it was possible determined that of 29 patients with OFA ≤ 3, 20 had DI > 0.3. These findings demonstrated that phenotypic healthy dogs according to OFA grading can present passive hip joint laxity, as demonstrated by radiographic evaluation with distraction. Furthermore, DI can contribute to the screening of CHD when evaluated in conjunction with OFA grading.